„Eu fui făcătoriu de pace, ca mielu cu lupu”: evaluarea din perspectiva autorului în „Cronica Banatului” de Nicolae Stoica de Haţeg - Raluca Levonian (Revista de Istorie și Teorie Literară)
This study aims to investigate the realization of authorial evaluation within a particular type of text, a Romanian chronicle written in the first half of the 19th century by the priest Nicolae Stoica. The theoretical framework is based on the definition of evaluation and on the four key parameters of evaluation identified by Thompson and Hunston (2001). The results show that all the parameters are represented in the text and that the use of this scheme allows a structured investigation of the various occurences of evaluative fragments within the text analyzed. However, there are also instances of evaluation, as irony or humorous evaluation, for example, which can be explained only through a more refined analysis.